Epirubicin-calf thymus DNA interaction: a comprehensive investigation using molecular docking, spectroscopy and fluorescent quantum dots - Hemati Azandaryani, Abbas; Barati, Ali; Shahlaei, Mohsen; Shamsipur, Mojtaba; Moradi, Sajad; Arkan, Elham (Cellular and Molecular Biology, 2018)
Reviewing the mode of interaction between this kind of active pharmaceutical ingredients and DNA has received much more attention in current years. Anthracycline drugs such as Epirubicin are frequently used in cancer treatment for breast cancer treatment. In the present study, the Epirubicin -calf thymus DNA interaction was investigated by using spectroscopic, fluorimetric and molecular docking methods. Water-soluble quantum dots (QDs) with nanometric particle size fabricated and characterized by transmission electron microscope and photon correlation spectroscopy. The binding constant value and the free energy change for this interaction were obtained to be 3.00í—106 M-1 and -42.26 kJ mol-1, using the spectroscopic method and docking investigations, respectively. Additionally, fluorescent thioglycolic acid-capped CdTe QDs were used for investigation of EPI and DNA interaction. Epirubicin as a quencher quenched the fluorescence of CdTe QDs after electrostatic adsorption on the surface of QDs. With the addition of DNA, EPI will be desorbed from the surface of CdTe QDs, inserted into the DNA. Subsequently, fluorescence changes of QDs were used for calculation of binding constant value, which was in good agreement with that obtained by the spectroscopic method. By the comparison of the achieved results, the intercalation mode of interaction between Epirubicin and DNA proved.